Dotación de servicios básicos y desarrollo social en la comuna San José, cantón Santa Rosa. año 2020 - Encarnación Castillo, Jeniffer Denisse; Ríos Sarango, Nancy Andrea (Machala: Universidad Técnica de Machala, 2021)
The provision of basic services with quality standards contributes to the satisfaction of basic needs and, at the same time, to the improvement of the living conditions of all the inhabitants, facilitating the community Good Living and social development. However, despite the fact that great achievements have been made over time in matters of society, well-being and harmony, at present, the lack of basic services of the first order is still latent in some lagging neighborhoods and communities of Ecuador. , complementary and protective, generated by an inequitable and unfair investment of public spending, thus limiting not only compliance with a constitutional but also universal right. In such virtue, the present research work focused on the Provision of basic services and social development in the San José Commune, Santa Rosa canton was proposed. Year 2020. Which sets out as its main objective, to determine the significance in social development generated by the inadequate provision of basic services in the San José Commune, and as specific objectives the characterization of current social development, establishment of the types of basic services existing in the commune, identification of the causal factors that affect the adequate provision of basic services, and the determination of the consequences on social development generated by the unsatisfactory provision of basic services in the San José Commune. The methodology used is quantitative in nature, with a sociological foundation in Talcott Parsons' structural functionalism and Buen Vivir as an alternative civilizing paradigm, whose epistemological approach is the empirical-inductive philosophically supported by logical positivism, applying data collection techniques to observation, the socio-economic census and the community workshop, which contributed to the identification of the existing problems. Through the empirical results obtained, it was possible to determine that the provision of basic services is incomplete and unsatisfactory due to the almost null intervention of the Autonomous Decentralized Government GAD of the Bellavista parish and the Santa Rosa canton, this added, to the weak cohesion, social organization, inefficient leadership and directive management by the community, ultimately generating a high deficit in social development in the locality. Based on a feasibility analysis, the development of a training program for strengthening social cohesion and organization, leadership and proactive community management is proposed as an interventional proposal, aimed at improving the provision of basic services as a fundamental support for harmonious and sustained social development, supported by art. 66 of the Constitution of the Republic of Ecuador The right to a dignified life, which ensures health, food and nutrition, drinking water, housing, environmental sanitation, education, work, employment, rest and leisure, physical culture, clothing, security social and other necessary social services ASAMBLEA NACIONAL CONSTITUYENTE, 2008. Linking with the reason for being of the Technical University of Machala, by training competent student researchers who make use of their knowledge to contribute to the development of society framed in solid values such as humanism.
La prestación de servicios básicos con estándares de calidad coadyuva a la satisfacción de las necesidades básicas y, a la vez, al mejoramiento de las condiciones de vida de todos los habitantes, viabilizando el Buen Vivir comunitario y el desarrollo social. Sin embargo, a pesar de que se han alcanzado grandes logros con el transcurso del tiempo en temas de sociedad, bienestar y armonía, en la actualidad, aún está latente en algunos barrios y comunidades rezagados del Ecuador la carencia de los servicios básicos de primer orden, complementarios y de protección, generados por una inequitativa e injusta inversión del gasto público, coartando así no solamente el cumplimiento de un derecho constitucional sino también universal. En tal virtud, se planteó el presente trabajo de investigación focalizado en la Dotación de servicios básicos y desarrollo social en la Comuna San José, cantón Santa Rosa. Año 2020, el cual expone como objetivo principal, determinar la trascendencia en el desarrollo social que genera la inadecuada dotación de servicios básicos en la Comuna San José, y como objetivos específicos la caracterización del actual desarrollo social; establecimiento de los tipos de servicios básicos existentes en la comuna; identificación de los factores causales que afectan la adecuada dotación de servicios básicos; y, la determinación de las consecuencias en el desarrollo social que genera la insatisfactoria dotación de servicios básicos en la Comuna San José. La metodología empleada es de naturaleza cuantitativa, con fundamento sociológico en el funcionalismo estructural de Talcott Parsons y el Buen Vivir como paradigma civilizatorio alternativo, cuyo enfoque epistemológico es el empírico-inductivo sustentado filosóficamente en el positivismo lógico, aplicándose como técnicas de recolección de datos la observación, el censo socio económico y el taller comunitario, mismos que contribuyeron a la identificación de las problemáticas existentes. A través de los resultados empíricos obtenidos se logró determinar que la prestación de servicios básicos es incompleta e insatisfactoria a causa de la casi nula intervención del Gobierno Autónomo Descentralizado GAD de la parroquia Bellavista y del cantón Santa Rosa, esto sumado, a la débil cohesión, organización social, ineficiente liderazgo y gestión directiva por parte de la comunidad, generando finalmente un alto déficit en el desarrollo social en la localidad. En base a un análisis de factibilidad se plantea como propuesta interventiva la elaboración de un Programa de capacitación para el fortalecimiento de la cohesión y organización social, el liderazgo y la gestión comunitaria proactiva, direccionado al mejoramiento de la dotación de servicios básicos como soporte fundamental para el desarrollo social armónico y sostenido, sustentado en el art. 66 de la Constitución de la República del Ecuador El derecho a una vida digna, que asegure la salud, alimentación y nutrición, agua potable, vivienda, saneamiento ambiental, educación, trabajo, empleo, descanso y ocio, cultura física, vestido, seguridad social y otros servicios sociales necesarios ASAMBLEA NACIONAL CONSTITUYENTE, 2008. Vinculándose con la razón de ser de la Universidad Técnica de Machala, al formar estudiantes investigadores competentes quienes hacen uso de sus conocimientos para aportar al desarrollo de la sociedad enmarcados en valores sólidos como el humanismo.
Keywords: SERVICIO BASICO; DESARROLLO SOCIAL; SAN JOSE